Integrating Human Centered Management and Circular Economy for Sustainable Business Growth - Sipakoly, Selly (Jurnal Informatika Ekonomi Bisnis, 2025)
This study examines the strategic integration of Human-Centered Management (HCM) and Circular Economy (CE) as a pathway to achieve sustainable business growth. The scope of the research focuses on understanding how human capabilities, organizational culture, and regenerative resource systems interact to support long-term sustainability performance. The objective is to develop an integrated conceptual model that connects human-centered values with circular practices. The study employs a qualitative-descriptive approach supported by systematic literature analysis. Data were collected from reputable scientific databases and screened based on relevance, recency, and academic quality. The findings reveal dominant HCM themes such as empowerment, participatory leadership, capability development, and meaningful work, which collectively strengthen employee readiness for circular innovation. CE themes identified include eco-design, life-cycle extension, resource recovery, closed-loop production, and collaborative supply chains. The results show that the synergy of HCM and CE enhances innovation capability, operational efficiency, workforce engagement, and value chain resilience. The study concludes that integrating human-centered values and circular strategies provides a solid foundation for regenerative and future-ready business models. Recommendations for further research include empirical testing of the proposed model and sector-specific implementation analysis.